ZAKAT DISTRIBUTION IN BAZNAS GROBOGAN REGENCY ACCORDING TO LAW NUMBER 23 YEAR 2011 CONCERNING ZAKAT MANAGEMENT (Case Study at UPZ Toroh District, Grobogan Regency in 2022) - Septiya Yuliatik (JIL : Journal of Indonesian Law, 2022)
The distribution of zakat is the process of distributing zakat that has been collected to mustahik which aims to create equitable community welfare. BAZNAS Grobogan Regency is a national zakat management institution with a large area and the majority Muslim population. So, zakat really needs to get attention seeing its great potential. This writing aims to find out how the distribution of zakat in BAZNAS in Grobogan Regency is evenly distributed and how the distribution of zakat in BAZNAS in Grobogan Regency is from the perspective of Law Number 23 of 2011 concerning Zakat Management. The writing method used is a qualitative method with a sociological juridical approach. Data collection was obtained from interviews with BAZNAS in Grobogan district and UPZ in Toroh sub-district. Then, this data analyzed using regulations on zakat, namely Law Number 23 of 2011 concerning Zakat management. The results of this research are in the implementation of the distribution of zakat, BAZNAS Grobogan Regency formed UPZ (Zakat Collector Unit) that located in each District. BAZNAS Grobogan Regency has 19 (nineteen) UPZ, one of which is Toroh District UPZ. The distribution of zakat in BAZNAS in Grobogan Regency is carried out in accordance in Articles 25 and 26 of Law Number 23 of 2011 concerning Zakat Management. However, efforts are needed in order to optimize distribution in UPZ Toroh District. Thus, the distribution of zakat can reach the indigent mustahik who are the area coverage of the UPZ.